2020
DOI: 10.1021/acs.iecr.0c01666
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Process for the Production of Lactic Acid from Lignocellulosic Biomass: From Biomass Fractionation and Characterization to Chemocatalytic Conversion with Lanthanum(III) Triflate

Abstract: The development of green processes for the production of renewable chemicals from biomass is required to respond to environmental issues. Herein, we report an integrated process for the production of lactic acid from lignocellulosic biomass. Lactic acid, one of the most important building block chemicals for producing biodegradable plastics, is of great interest in biorenewable communities. Selective fractionation of a hemicellulose-rich stream, almost 90% recovery, was conducted using a lab-scale flowthrough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
0
8
0
3
Order By: Relevance
“…While further prolonging the reaction time from 30 to 120 min resulted in an almost complete conversion of cellulose and an equilibrated trend of lactic acid yield, whereas the yields of HMF, glyceraldehyde and acetol decreased gradually, simultaneously, it was observed that the amount of the black polymer progressively increased in the reaction solution, probably as a result of the decomposition of lactic acid produced and polymerization or rehydration of HMF in the presence of acidic condition [12] . At first, the formation of lactic acid and HMF possessed a competitive relationship, and their yields significantly increased with prolonging the time, and then underwent further rehydration of HMF to formic acid and levulinic acid, as well as the occurrence of side‐reactions in acidic condition, consequently resulting in decreasing the yield of HMF and increasing yields of formic acid and levulinic acid [7a,13,26] …”
Section: Resultsmentioning
confidence: 98%
“…While further prolonging the reaction time from 30 to 120 min resulted in an almost complete conversion of cellulose and an equilibrated trend of lactic acid yield, whereas the yields of HMF, glyceraldehyde and acetol decreased gradually, simultaneously, it was observed that the amount of the black polymer progressively increased in the reaction solution, probably as a result of the decomposition of lactic acid produced and polymerization or rehydration of HMF in the presence of acidic condition [12] . At first, the formation of lactic acid and HMF possessed a competitive relationship, and their yields significantly increased with prolonging the time, and then underwent further rehydration of HMF to formic acid and levulinic acid, as well as the occurrence of side‐reactions in acidic condition, consequently resulting in decreasing the yield of HMF and increasing yields of formic acid and levulinic acid [7a,13,26] …”
Section: Resultsmentioning
confidence: 98%
“…In an attempt to make these catalysts heterogeneous, Kim et al (2020) impregnated La(OTf) 3 on SiO 2 , but metal leaching and coke were detected, leading to poor reusability. 10 As for transition metal salts, oxidation state is a determining parameter for catalytic activity. Although a significant product distribution difference was observed between SnCl 2 (33% LA yield) and SnCl 4 (24% LA yield), it is unclear how the degree of oxidation of Sn affects the reaction mechanism.…”
Section: Acs Omegamentioning
confidence: 99%
“…Biomass monosaccharides such as glucose rapidly degrade under hydrothermal conditions to multiple products, of which LA is produced in small yields. , A large range of homogeneous and heterogeneous catalysts have been tested to convert glucose to LA over the last 20 years. Among them, rare metal salts have been identified as the most efficient homogeneous catalysts due to their high Lewis acidities, achieving LA yields over 85%. Such a performance has yet to be achieved in heteregeneous catalytic systems due to leaching of the rare metal species. , Other metal salt combinations that tune the Lewis acidity improve LA yield. Hierarchical bimetallic Sn-Beta zeolite is the most promising heterogeneous catalyst due to its pore system and Lewis acidity leading to LA yields over 65%. Other bifunctionalized aluminosilicates attain LA yields over 60% due to their well-tuned Lewis acidities accelerating the rate-determining retro-aldol decomposition of fructose.…”
Section: Introductionmentioning
confidence: 99%
“…With the gradual weakening of the carrying capacity of resources and the environment, my country has realized the importance and urgency of low-carbon development of the power industry, and has taken a series of measures to strengthen the control of pollutants generated in the PG process. In the context of low carbon, one of the main ways is to give priority to the development of CE with zero carbon emissions in PGP, and to continuously optimize the power structure [7][8].…”
Section: Goals and Principles Of Grid Planningmentioning
confidence: 99%